Obtenção e caracterização de revestimentos antimicrobianos de silicone com nanopartículas de prata (PDMS/AgNPs) para uso em embalagens ativas, utensílios e equipamentos via solution blow spraying - SBSp - Ferreira, Thiago Péricles Martins (2015)
In this work, poly coatings were obtained (dimethyl siloxane) with silver nanoparticles (PDMS / AgNPs), produced by the method of solution blow spraying (SBSp), a technique of adapting Solution Blow Spinning (SBS), with potential for application in packaging and equipment coatings in the food industry. AgNPs synthesized by Turkevich method were deposited on the PDMS film SBSp technique and tested antimicrobial activity against microorganisms S. aureus and E. coli (ATCC). The results of dynamic light scattering (DLS) showed that AgNPs had an average size of 170,5 nm. In addition, these nanoparticles show antimicrobial activity, in accordance with the disk diffusion test, and were considered for nontoxic toxicity tests against Artemia salina. The AgNPs were deposited on the PDMS films at various intervals cure this resin. Scanning electron microscopy (SEM) allowed the observation that the films form uniform coatings with a thickness of 1,62 ± 0,2μm and the particles are evenly distributed over the surface of the film (SEM-EDS) with concentrations varying according to the time and number of depositions of AgNPs. These results were also corroborated by atomic force microscopy (AFM) and atomic emission spectrometry with inductively coupled plasma (ICP / AES). When the application of AgNPs was performed at the end or after the course of ¾ PDMS curing time, there was a greater reduction in cell adhesion and biofilm formation uniespécie for S. aureus and E. coli (ATCC). This reduction has also been improved when multiple applications AgNPs were made. Once all coatings showed antimicrobial activity, their use in food industry can be considered promising.